97.0k views
3 votes
Solve using the substitution method.​

Solve using the substitution method.​-example-1

2 Answers

4 votes
It would be equal to 3
User Eric Boehs
by
5.6k points
2 votes

Answer:

The solution is d = 3 and e = -1

Explanation:

To solve using the substitution method, we need to first solve the second equation for d.

d - e = 4

d = e + 4

Now that we have the value of d, we can put it in for d in the first equation and solve for e.

d + e = 2

(e + 4) + e = 2

2e + 4 = 2

2e = -2

e = -1

Now that we have this value, we can plug it into the original equation and find d.

d + e = 2

d + -1 = 2

d = 3

User Mrgou
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.